72.4k views
5 votes
How to solve y-b/x=m for y

User Eric MJ
by
5.4k points

2 Answers

6 votes
To solve for m we want to get m by itself on one side of the equals sign, with everything else on the other side. First we subtract b from both sides, to get it out of the right side of the equation:
y - b = mx + b - b
y - b = mx
Now we divide both sides by x, to get m completely by itself:
(y-b)/x = (mx)/x
(y-b)/x = m
So m is equal to (y-b)/x.
User Blanco
by
5.8k points
5 votes

Answer:

Explanation:

y - b/x = m

Adding b/x both sides

y = m+b/x

But i think your question you're trying to ask is (y - b)/x = m

So, for this one,

Multiply both sides by x

y-b = mx

Adding b both sides

To get: y=mx+b

Hope this helps!

User Aditya
by
5.2k points